First serological evidence of Coxiella burnetii and Mycobacterium avium subspecies paratuberculosis (MAP) among deer in an institutional farm in Malaysia - Abdullah, Faez Firdaus Jesse; Lim, Eric Teik Chung; Mohd Lila, Mohd Azmi; Thlama, Bura Paul; Sundar, Shivnraj; Yosryhan, Nur Hanis Nadhirah; Ahmed Jimale, Yonis; Norsidin, Mohd Jefri; Azhar, Nur Amira (Faculty of Veterinary Science, Chulalongkorn University, 2024)
Q fever is a zoonotic disease caused by Coxiella burnetii, which is associated with reproductive disorders such as abortion and reproductive problems in ruminants, while paratuberculosis is an underdiagnosed disease caused by Mycobacterium avium paratuberculosis (MAP) which causes chronic wasting, low fertility, and mortality in ruminants. Although both C. burnetii and MAP infections have been reported in domestic ruminants worldwide, there is no data on their seroprevalence status among deer in Selangor, Malaysia. This study investigated the seroprevalence status of C. burnetii and MAP among deer in Malaysia. Ninety-two blood sera collected from an institutional deer farm were screened using commercial Multi-species ID Screen indirect ELISA tests to detect specific anti-C. burnetii (FQS-MS/1117) and anti-MAP (PARAS Ver 0516) antibodies. The ELISA results showed a 14.1% (95% CI = 8.5-22.7) apparent and 14.8% (95% CI = 8.4-24.4) true prevalence for C. burnetii and a 2.2% (95% CI= 0.6-7.6) apparent and 1.3% (95% CI= -0.45-7.40) true prevalence for MAP among deer. There were statistically significant associations between seropositivity to C. burnetii and the age groups (χ2= 7.325, P = 0.011) or herds of deer (χ2= 9.732, P = 0.001). To the best of our knowledge, this study provides the first preliminary serological evidence of C. burnetii and MAP in Cervus timorensis, suggesting potential threats to animal and public health in Malaysia.